Expression and function of Neuregulin 1 and its signaling system ERBB2/3 in the enteric nervous system - Barrenschee, Martina; Lange, Christina; Cossais, François; Egberts, Jan-Hendrik; Becker, Thomas; Wedel, Thilo; Böttner, Martina (Frontiers in Cellular Neuroscience, 2015)
Neuregulin 1 (NRG1) is suggested to promote the survival and maintenance of the enteric nervous system (ENS). As deficiency in its corresponding receptor signaling complex ERBB2/ERBB3 leads to postnatal colonic hypo/aganglionosis we assessed the distributional and expressional pattern of the NRG1-ERBB2/ERBB3 system in the human colon and explored the neurotrophic capacity of NRG1 on cultured enteric neurons. Site-specific mRNA expression of the NRG1-ERBB2/3 system was determined in microdissected samples harvested from enteric musculature and ganglia. Localization of NRG1, ERBB2 and ERBB3 was determined by dual-label-immunohistochemistry using pan-neuronal and pan-glial markers. Morphometric analysis was performed on NRG1-stimulated rat enteric nerve cultures to evaluate neurotrophic effects. mRNA expression of the NRG1-ERBB2/3 system was determined by qPCR. Co-localization of NRG1 with neuronal or synaptic markers was analyzed in enteric nerve cultures stimulated with glial cell line-derived neurotrophic factor (GDNF). The NRG1 system was expressed in both neurons and glial cells of enteric ganglia and in nerve fibers. NRG1 significantly enhanced growth parameters in enteric nerve cell cultures and ErB3 mRNA expression was down-regulated upon NRG1 stimulation. GDNF negatively regulates ErbB2 and ErbB3 mRNA expression The NRG1-ERBB2/3 system is physiologically present in the human ENS and NRG1 acts as a neurotrophic factor for the ENS. The down-regulation of ErbB3/ErbB2 in GDNF stimulated nerve cell cultures points to an interaction of both neurotrophic factors. Thus, the data may provide a basis to assess disturbed signaling components of the NRG1 system in enteric neuropathies.